2005
DOI: 10.1021/ct050029z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of N-Methylacetamide Revisited by ab Initio Molecular Dynamics Simulations

Abstract: The density functional theory based molecular dynamics simulation method ("Car-Parrinello") was applied in a numerical study of the electronic properties, hydrogen bonding, and infrared spectroscopy of the trans and cis isomer of N-methylacetamide in aqueous solution. A detailed analysis of the electronic structure of the solvated molecules, in terms of localized Wannier functions and Born atomic charges, is presented. Two schemes for the computation of the solute infrared absorption spectrum are investigated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
221
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(248 citation statements)
references
References 80 publications
18
221
0
2
Order By: Relevance
“…Although normalmode analysis of quasirigid molecules in the gas phase nowadays has become a standard tool, the computation of IR spectra in dynamically interacting environments, such as condensed phases or biomolecular matrices, is much more intricate, if based on electronic structure calculations (24,(29)(30)(31)(32)(33)(34). Furthermore, a peculiar challenge is posed by the strongly anharmonic and flat potential energy surfaces as typically encountered by excess protons in hydrogen-bonded networks (20) such as WLANs, which challenges the harmonic approximation.…”
mentioning
confidence: 99%
“…Although normalmode analysis of quasirigid molecules in the gas phase nowadays has become a standard tool, the computation of IR spectra in dynamically interacting environments, such as condensed phases or biomolecular matrices, is much more intricate, if based on electronic structure calculations (24,(29)(30)(31)(32)(33)(34). Furthermore, a peculiar challenge is posed by the strongly anharmonic and flat potential energy surfaces as typically encountered by excess protons in hydrogen-bonded networks (20) such as WLANs, which challenges the harmonic approximation.…”
mentioning
confidence: 99%
“…The atomic electric dipole moments computed following Eq. (27) are, similar to Mulliken atomic charges, 163 rather basis set dependent. Nevertheless, it can be concluded that the increase of the absolute electric dipole moment of a liquid EC molecule compared to the one of a gas phase EC molecule (all obtained with the TZVP-GTH basis set) mostly arises from distinct contributions from its carbonyl group.…”
Section: Example Applications: Ec and Dmcmentioning
confidence: 93%
“…(27). The atomic electric dipole moment origin was set to the same origin as the one of the corresponding molecular electric dipole moment (i.e., the center of charge of the subsystem).…”
Section: Example Applications: Ec and Dmcmentioning
confidence: 99%
See 2 more Smart Citations